Coffee elite in Colombia and its participation in the Foreign Policy during the first half of the 20th century: Elite do café na Colômbia e sua participação na Política Externa durante a primeira metade do século XX - Martinez Villalba, Yulieth Estefani (Conjuntura internacional, 2019)
This paper aims to bring some reflections of political-sociological contents of Colombian foreign policy by analyzing the participation of the coffee elite in the foreign trade policy during the first half of the 20th century, making evident the transcendence of the of National Federation of Coffee Growers (NFCG) and its leaders in the orientation of Colombia's foreign trade policy.